1997
DOI: 10.1038/nm1197-1228
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-associated signaling pathways are required for chemotherapy-mediated female germ cell destruction

Abstract: Female sterility resulting from oocyte destruction is an unfortunate, and in many cases inevitable, consequence of chemotherapy. We show that unfertilized mouse oocytes exposed to therapeutic levels of the antitumor drug, doxorubicin (DXR), undergo apoptosis; however, fertilized oocytes do not initiate apoptosis, but enter cell-cycle arrest, when treated with DXR. Apoptosis induced by DXR in oocytes is blocked by sphingosine-1-phosphate, an inhibitor of ceramide-promoted cell death. Oocytes from Bax-deficient,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
247
1
9

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 336 publications
(274 citation statements)
references
References 45 publications
17
247
1
9
Order By: Relevance
“…Lack of p53 transcript recruitment observed in the present study as well as its dispensability in the DXR-mediated death reported previously, 10 further supports the hypothesis that, other members of p53 surveillance proteins may be involved in DXR modulations. Discovery of two other p53 family members (p63 and p73) which share many molecular features of p53 apoptosis induction makes these molecules excellent candidates for modulating DXRmediated death pathways in oocytes.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Lack of p53 transcript recruitment observed in the present study as well as its dispensability in the DXR-mediated death reported previously, 10 further supports the hypothesis that, other members of p53 surveillance proteins may be involved in DXR modulations. Discovery of two other p53 family members (p63 and p73) which share many molecular features of p53 apoptosis induction makes these molecules excellent candidates for modulating DXRmediated death pathways in oocytes.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, as in our previous report, 10 DXR induced high rate of oocyte fragmentation (5374.8%, n ¼ 397; Po0.001), whereas spontaneous rate of cytoplasmic fragmentation was low in unexposed oocytes (6.472.5%, n ¼ 414).…”
Section: Dxr Induces Early Dna Damage Late Activation and Fragmentationsupporting
confidence: 88%
See 3 more Smart Citations